2009
DOI: 10.1186/1476-7120-7-41
|View full text |Cite
|
Sign up to set email alerts
|

Visually estimated ejection fraction by two dimensional and triplane echocardiography is closely correlated with quantitative ejection fraction by real-time three dimensional echocardiography

Abstract: Background: Visual assessment of left ventricular ejection fraction (LVEF) is often used in clinical routine despite general recommendations to use quantitative biplane Simpsons (BPS) measurements. Even thou quantitative methods are well validated and from many reasons preferable, the feasibility of visual assessment (eyeballing) is superior. There is to date only sparse data comparing visual EF assessment in comparison to quantitative methods available. The aim of this study was to compare visual EF assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 20 publications
8
52
1
2
Order By: Relevance
“…By the design of the present study, the LVEF assessment at the recruiting hospital was done either by visual assessment, Simpson's biplane or area length assessment, and thus the 95 % confidence interval of the differences do not represent a strict measurement of interobserver variability. Nevertheless, the variabilities in our study correspond to previously published values of interobserver variability [19,20], while others have published lower values [21][22][23]. An important difference A B C Fig.…”
Section: Interobserver Reliabilitycontrasting
confidence: 33%
“…By the design of the present study, the LVEF assessment at the recruiting hospital was done either by visual assessment, Simpson's biplane or area length assessment, and thus the 95 % confidence interval of the differences do not represent a strict measurement of interobserver variability. Nevertheless, the variabilities in our study correspond to previously published values of interobserver variability [19,20], while others have published lower values [21][22][23]. An important difference A B C Fig.…”
Section: Interobserver Reliabilitycontrasting
confidence: 33%
“…LVEF was calculated using Simpson's biplane method, taking great care to avoid foreshortening when acquiring apical images. CVs of our laboratory for Simpon's biplane method have been published previously as intraobserver CV: 2.3-3.8% and interobserver CV: 7.5-8.4% (45). Dynamic mitral regurgitation was specifically excluded using Doppler imaging (32) Color-coded tissue Doppler data were obtained by postprocessing at a dedicated workstation (EchoPAC; GE Healthcare, Horten, Norway) All cardiac dimensions, blood flow, and velocities were analyzed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, worldwide availability of echocardiography is surely greater. Furthermore, several recent studies have shown the excellent interobserver and intraobserver reproducibility of echocardiographic evaluation on LVEF [15,16]. This has been evaluated as similar to that of cardiac magnetic resonance (CMR), even in patients with TM [17].…”
mentioning
confidence: 93%